Financial Deepening And Financial Performance Of Deposit Money Banks In Nigeria - Yusuff, Mulkat Ajibola; Olaniran-Akinyele, Fatimah Olabisi (Advances in Social Sciences Research Journal, 2019)
This study examines the effect of financial deepening on financial performance of Nigerian Deposit Money Banks using time-series data spanning 1990Q1-2017Q4. The financial performance is expressed by return on assets (ROA) and return on equity (ROE) with total bank liability, private sector credit and market capitalization as measure of financial deepening. The technique of analysis deployed is autoregressive distributed lag (ARDL) to co integration. The findings show that the effect of total bank liability is positive and significant. Market capitalization and private sector credit on the other hand exert negative and significant effect. The study concludes that financial deepening affect financial performance of Deposit Money Banks in Nigeria. It then recommends effective loan recovery strategy to mitigate the negative influence of private sector credit due to non-performing loans.